شاعرية النص الأنثوي في شعر أشجان هندي : دراسة أسلوبية بلاغية - شريف، تيسير عباس محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This study deals with the poetry of Ashjan Hindi based on her stylistic rhetorical practical style. Where Saudi poets in general and Ashjan in particular have a place in modern Arabic literature, and have special features that distinguish them from others. The study also examines the stylistic rhetorical features of Ashjan Hindi based on her collection of poems entitled Reeq Al-Ghaimat or “Saliva of the Clouds” which contains the subject of the study (two collections). The thesis starts by introducing Ashjan, by giving an overview of her life, the frames that were influential in her poetry, her literary output, and the linguistic construction that examines the connotations contained in the functions in different contexts. To clarify its relationship with the overall sense of the text starting with the individual structure, some textual thresholds in her poems, fields of connotations and her own poetic lexicon are discussed. Then the grammatical and rhetorical offsets in compositional structure as well as intertextuality, the gleam poem, and the technique of the reproduction of anecdotes and other infrastructure in the text also highlighted. The study also shows the rhythmic structure in its three dimensions: the external rhythm, internal rhythm and the text space rhythm, pointing to connotations derived as much as possible. Then the study also indicates the essence of the suggestive and aesthetic connotation in the pictorial structure through sensual, fixed and mobile, partial and cross, whole and fine images as well as swift images. The study utilised the inductive descriptive and analytical approaches based on tracing the stylistic outstanding phenomena in the poems of Ashjan, collecting and labeling them through identifying their characteristics and explicit existing relationships, and then interpreting, analyzing and extracting the meanings depending on the linguistic structure. The study concludes with several results, including the poet's creativity in making renewal and experimentation in the rhymes and poem structures, and her invention of modern formulas in producing new and profound implications. Her poems are also considered as displacing poetic and rhetorical portraits with suggestive and aesthetic horizons, her use of intertextuality and multiple voices in polyphonic poems and the hybridization which is an artistic phenomena of polyphony.